2012
DOI: 10.1155/2012/948652
|View full text |Cite
|
Sign up to set email alerts
|

Brönsted Acidic Ionic Liquid 1-(1-Propylsulfonic)-3-methylimidazolium-Chloride Catalyzed Hydrolysisof D-Cellobiose in Aqueous Medium

Abstract: Brönsted acidic ionic liquid 1-(1-propylsulfonic)-3-methylimidazolium chloride (PSMIMCl) shows a higher catalytic activity than sulfuric acid in the hydrolysis of D-cellobiose to D-glucose in water at 90-120• C. This catalytic activity enhancement is more significant at higher temperatures, and at 120• C, PSMIMCl produced 64.5% glucose yield, whereas H 2 SO 4 produced only 42.2% after 40 min. reaction, and this is a 52.8% enhancement of catalytic activity due to the alkylimidazolium group attached to the sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…681 In addition, hydrolysis of a cellulose model compound in water also supported the observation of enhanced catalytic activity of −SO 3 H functionalized imidazolium BAILs in water in comparison to H 2 SO 4 . 682 Structure−activity relationships in a series of −SO 3 H functionalized imidazolium, pyridinium, trialkylammonium BAILs have revealed that single −SO 3 H attached imidazolium catalysts are more effective than pyridinium and trialkylammonium types in cellulose hydrolysis in water at moderate temperature−pressure conditions. 683 A number of research groups have studied acidic ionic liquids immobilized on a solid supports, which include; graphene-like nanoporous carbons, 684 silica, 225,233 and polystyrene 282 for the depolymerization of cellulose as well as various lignocellulosic biomass forms.…”
Section: Membrane Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…681 In addition, hydrolysis of a cellulose model compound in water also supported the observation of enhanced catalytic activity of −SO 3 H functionalized imidazolium BAILs in water in comparison to H 2 SO 4 . 682 Structure−activity relationships in a series of −SO 3 H functionalized imidazolium, pyridinium, trialkylammonium BAILs have revealed that single −SO 3 H attached imidazolium catalysts are more effective than pyridinium and trialkylammonium types in cellulose hydrolysis in water at moderate temperature−pressure conditions. 683 A number of research groups have studied acidic ionic liquids immobilized on a solid supports, which include; graphene-like nanoporous carbons, 684 silica, 225,233 and polystyrene 282 for the depolymerization of cellulose as well as various lignocellulosic biomass forms.…”
Section: Membrane Applicationsmentioning
confidence: 99%
“…For example, Sigmacell cellulose (DP ∼ 450) in aqueous solutions of 1-(1-propylsulfonic)-3-methylimidazolium chloride, p -toluenesulfonic acid, and sulfuric acid of the same acid strength (0.0321 mol H + ion/L) produced total reducing sugar (TRS) yields of 28.5, 32.6, and 22.0% respectively, after heating at 170 °C for 3.0 h. In the same set of experiments 22.2, 21.0, and 16.2% glucose yields were attained in 1-(1-propylsulfonic)-3-methylimidazolium chloride, p -toluenesulfonic acid, and sulfuric acid mediums, respectively . In addition, hydrolysis of a cellulose model compound in water also supported the observation of enhanced catalytic activity of −SO 3 H functionalized imidazolium BAILs in water in comparison to H 2 SO 4 . Structure–activity relationships in a series of −SO 3 H functionalized imidazolium, pyridinium, trialkylammonium BAILs have revealed that single −SO 3 H attached imidazolium catalysts are more effective than pyridinium and trialkylammonium types in cellulose hydrolysis in water at moderate temperature–pressure conditions .…”
Section: Applications Of Acidic Ionic Liquidsmentioning
confidence: 99%
“…The effectiveness of pretreatment is predicted using the Kamlet-Taft hydrogen bond acceptor ability, : usually, the higher values of translate to higher lignin removal and vice versa [177]. It is known that component ions in ILs influence enzyme activity [178] and stability [173], and the anion-as a result of its hydrogen basicity-attacks and breaks the hydrogen bonds of cellulose structure [179] by forming hydrogen bonds with the cellulose [180]. Thus, the cellulose is solubilised and the crystalline nature is reduced [181] via cell wall swelling resulting from dislocation of hydrogen bonds between cellulose fibrils and lignin [182], partial removal of hemicellulose, and biomass delignification [183].…”
Section: Process Description and Mechanismmentioning
confidence: 99%
“…ILs with high viscosities have low potential in terms of mass and phase transfer which presents challenges in engineering applications [165,175]. Moreover, the separation of hydrophilic ILs and monomeric sugars in water is difficult [178,204]. Some ILs also exhibit tendencies to denature enzymes [168] and the active sites of enzymes could be blocked by layers of hydrophilic ILs, decreasing or destroying the aqueous phase surrounding enzyme surface [173].…”
Section: Drawbacks and Process Modificationsmentioning
confidence: 99%
“…As recent studies of using metal ions and particularly transition metal ions are shown to enhance the mineral acid catalyzed cellulose hydrolysis, we hypothesized that even better catalytic effect enhancements can be expected for BAIL catalyzed cellulose hydrolysis. Therefore, in an attempt to test this hypothesis and to develop efficient acid catalyst system for cellulose ethanol process as well as an extension of our earlier work [19,25,21,20,26], we have studied the effect of metal ions as co-catalysts on 1-(1-propylsulfonic)-3-methylimidazolium chloride acidic ionic liquid catalyzed hydrolysis of cellulose in water as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%